The prevalence of PTSD and coping strategies among Palestinian mental health professionals during political violence and wartime - Ahmead, Muna; Abu Turki, Mariam; Fawadleh, Louy (Frontiers in Psychiatry, 2024)
In times of war, mental health professionals are at an increased risk of developing psychological problems, including post-traumatic stress disorder (PTSD). The effects of conflicts or wars on mental health professionals in Palestine and their coping methods of dealing with these challenges remain unknown. This study aimed to assess the prevalence of PTSD symptoms and strategies for coping among mental health professionals in Palestine, in light of the ongoing Gaza War and political violence.The study utilized a cross-sectional research design. Self-reported questionnaires, including the PCL-5 and Brief COPE scales, were used to gather data. The relationship between the research variables and PTSD symptoms was investigated using frequencies, percentages, bivariate analysis, Pearson correlation, and Pearson's chi-square test.A total of 514 participants were recruited, with an estimated prevalence of post-traumatic stress disorder (PTSD) of 38.7%. Furthermore, the multivariate analysis revealed that having a prior history of trauma and feeling disabled or unable to deal with your patients during the current Gaza war and Israeli-Palestinian political violence increases the likelihood of developing PTSD symptoms. In addition, using venting, self-blame, and behavioral disengagement as coping strategies increases the likelihood of developing symptoms of PTSD. Also, using acceptance and substance use as coping strategies reduces the risk of developing PTSD symptoms.The findings revealed a high prevalence of post-traumatic stress disorder (PTSD) symptoms among mental health professionals during wartime and political violence. As a result, mental health professionals need immediate assistance in enhancing their mental well-being through supervision, psychotherapy, and comprehensive and continuous training.